Technology Management and Competitiveness - Naik, B. M. (Journal of Engineering Education Transformations, 1999)
The author summarizes the need for and importance of technology management in a developing country such as India. He analyses the current situation with respect to technology in industry and innovation capabilities in higher education institutions. He suggests that technology management should be given high priority by government, industry and higher education sector so that the country can respond more forcefully and resourcefully to global competition.